The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.069
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Collaboration with Mobile Social Media in Multiple-Organization Projects

Abstract: This study investigates the use of mobile social media as emerging collaboration tools by virtual teams. Based on the construal level theory, it develops a research model hypothesizes that collaboration tool effectiveness influence contextual performance and task performance through the mediation of procedure agreeability. In addition, geographic dispersion, team size and project duration serve as moderators as they reflect virtual collaboration complexity. Empirical findings support most hypothesized relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…Convergence duration was described by med2: "one month, two months, three months, you will do these [media] programmes, those programmes will not be enough to bring an impact on what we are trying to achieve". This offers contrary evidence to the findings of a previous study, which found that a project collaboration's long duration positively impacted the performance of stakeholders who used the social media tool WeChat in China (Yang et al, 2018).…”
Section: Overall Duration Influencecontrasting
confidence: 99%
See 2 more Smart Citations
“…Convergence duration was described by med2: "one month, two months, three months, you will do these [media] programmes, those programmes will not be enough to bring an impact on what we are trying to achieve". This offers contrary evidence to the findings of a previous study, which found that a project collaboration's long duration positively impacted the performance of stakeholders who used the social media tool WeChat in China (Yang et al, 2018).…”
Section: Overall Duration Influencecontrasting
confidence: 99%
“…Two, igm prevention is demanding in nature. Previous findings reported that long-term collaboration occurs among distant stakeholders and that the negative impact of geographic dispersion has been reduced by using a technology-enabled tool (Righetto et al, 2019;Yang et al, 2018). On the other hand, an agreement on a suitable time for meetings was challenging in collaborations, especially at the start-up when collaboration formats were continuously reviewed (Ryan 2008).…”
Section: Overall Duration Influencementioning
confidence: 99%
See 1 more Smart Citation
“…And it was considered as providing timely, widespread data collection and dissemination as well as providing a reliable communication channel with teams [59]. Thus, organizations can utilize social media to facilitate the task of the teams and collaborate with them instead of face-toface meetings [60].…”
Section: Social Media (Sm)mentioning
confidence: 99%